Rationality of Antibiotic Use on Pneumonia Patients at dr. Doris Sylvanus Hospital Palangkaraya in 2022 - Nawan; Annisa, Farah; Handayani, Septi; Parhusip, Mual BE; Furtuna, Dewi; Trisia, Adelgrit; Toemon, Agnes I (Universitas Kristen Maranatha, 2025)
Pneumonia can be defined as a condition when a microorganism triggers inflammation of the lung parenchyma. The bronchioles and alveoli will be filled with inflammatory leukocyte exudate and fluid, causing respiratory difficulties and symptoms such as coughing, dyspnea, chest pain, and shock in severe cases. Pneumonia infections caused by bacteria can be treated with antibiotics. Bacterial patterns and sensitivity test results available at the hospital are used as a guide in selecting empiric therapy given to patients. Diagnostic limitations in differentiating viral and bacterial pathogens in pneumonia have led to increased use of antibiotics and contributed to the growth of antibiotic resistance. This research aims to determine the rationality of antibiotic use in pneumonia patients' resistance at RSUD dr.Doris Sylvanus Palangka Raya in 2022. A descriptive observational approach using a cross-sectional method was used to examine the medical records of pneumonia patients. Antibiotics commonly used by patients diagnosed with pneumonia at RSUD dr.Doris Sylvanus Palangka Raya in 2022 is Moxifloxacin with 153 patients (22.53%), then Levofloxacin with 143 patients (21.06%), and Ceftriaxone with 137 patients (20.18%). The total defined daily dose/100 days of antibiotics for pneumonia patients is 88.85 and according to the Gyssens criteria, the use of antibiotics is 82.62% rational.